Quark-gluon tagging: machine learning vs detector - Kasieczka, Gregor; Kiefer, Nicholas; Plehn, Tilman; Thompson, Jennifer M. (SciPost physics, 2019)
SciPost Journals Publication Detail SciPost Phys. 6, 069 (2019) Quark-gluon tagging: Machine learning vs detector
Gesehen am 09.11.2022